Vulva Haematoma following Sexual Assault in an Adolescent Nigerian Girl: A Case Report - S Nyeche; AE Ubom; JI Ikimalo (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Non-obstetric vulva haematomas are uncommon, with an incidence of 3.7% accounting for less than 1% of gynaecologic emergencies. Non-consensual sexual intercourse constitutes the most common aetiology. A 15-year-old adolescent Nigerian girl, who presented to the Gynaecologic Emergency Unit of the University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria, with vulva haematoma following sexual assault, is presented. She had surgical management, screening and prophylaxis for sexually transmitted infections, emergency contraception, and psychosocial therapy and was discharged after 24 hours, following an unremarkable postoperative period. This case is being reported to draw attention to the serious global public health problem of adolescent sexual abuse, highlight that though rare, vulva haematomas, which could be life-threatening, can be a complication of sexual assault, and review the literature on its management.